Pengaruh Current Ratio dan Total Asset Turnover Terhadap Return on Assets Pada Perusahaan Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2016 - Esti Paramita; Effendy Pakpahan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The purpose of this study was to determine the effect of Current Ratio and Total Assets Turnover both partially and simultaneously on Return On Assets in Food and Beverage Companies listed on the Indonesia Stock Exchange. The approach used in this study is the balance sheet and income statement of Food and Beverage Companies listed on the Indonesia Stock Exchange from 2012-2016.The independent variable used in this study consisted of Current Ratio and Total Assets Turnover, while the dependent variable was Return On Assets. Data collection techniques used in this study used the study of documentation. Data analysis techniques used multiple linear regression analysis, classic assumption test, t test, F test and coefficient of determination, with SPSS 16 software.The results of this study prove that the Current Ratio partially has an influence on Return On Assets and Total Assets Turnover also has an influence on Return On Assets. And simultaneously Current Ratio and Total Assets Turnover also has an influence on Return On Assets on Food and Beverage Companies listed on the Indonesia Stock Exchange.